2010
DOI: 10.1159/000277631
|View full text |Cite
|
Sign up to set email alerts
|

Insulin VNTR and IGF-1 Promoter Region Polymorphisms Are Not Associated with Body Composition in Early Childhood: The Generation R Study

Abstract: Objective: The objective of this study was to examine the associations between insulin gene variable number of tandem repeats (INS VNTR) and insulin-like growth factor 1 (IGF1) gene promoter region polymorphisms with body composition in early childhood. Methods: This study was embedded in an ongoing prospective cohort study. Growth in early childhood (body mass index, total subcutaneous fat mass and waist-hip ratio) was assessed at birth and at the ages of 6 weeks and 24 months. DNA for genotyping was availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172]. Although a GWAS is available in children, we use DNA from both children and parents for genotyping for candidate gene or replication studies [173][174][175][176][177][178][179][180][181][182]. Missing data in DNA samples in children will be collected by blood sampling or other methods at follow-up measurements.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Also, strategies for genetic scoring analyses are being developed to estimate predictive values of identified genetic variants [171,172]. Although a GWAS is available in children, we use DNA from both children and parents for genotyping for candidate gene or replication studies [173][174][175][176][177][178][179][180][181][182]. Missing data in DNA samples in children will be collected by blood sampling or other methods at follow-up measurements.…”
Section: Biological Samplesmentioning
confidence: 99%
“…In a general population, other authors also did not support associations between INS VNTR and body composition in childhood [25][26][27][28].…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, class III is protective against diabetes mellitus type 1 (T1DM) and leads to an overexpression of insulin [19][20][21]. Thus, it may be responsible for obesity, IR, T2DM, and polycystic ovary syndrome (PCOS); however, the results regarding the influence of INS VNTR polymorphism on these disorders, both in the general population and in SGA individuals, are divergent [10,13,15,17,[22][23][24][25][26][27][28][29]. The aim of the study was to verify whether INS VNTR class III allele is associated with low birth weight in the Polish population and to assess the influence of this variant on the current body mass index (BMI) as well as on the metabolic and hormonal profile in prepubertal SGA children.…”
Section: Introductionmentioning
confidence: 99%
“…However, they showed that the A/A genotype rather than the T/T genotype was associated with higher mean BMI and waist circumference (Huede et al 2004;Le Stunff et al 2001). In contrast, no significant associations between the INS polymorphisms with childhood and adult obesity among the Europeans (Bouatio-Naji et al 2008;Cimponeriu et al 2010), and with body composition in early childhood (Maas et al 2010) were reported. In our study, there was also lack of association between the INSR rs3745551 and childhood obesity in the Malay population.…”
Section: Discussionmentioning
confidence: 99%